OLIVER CROMWELL'S INFLUENCE ON LITERATURE AND ENLIGHTENMENT WRITES' POSITION TOWARDS HIM - Narxadjayeva Madina Abduvali qizi, Khamitov Eldorbek Erkinovich, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Oliver Cromwell, as a pivotal figure in 17th-century English history, significantly influenced literature and the intellectual climate of his time. His role as Lord Protector during the Interregnum shaped the themes, styles, and ideological perspectives of contemporary writers. Puritan values, political reforms, and social discipline under Cromwell’s regime found reflection in literature, particularly in moralistic and didactic writings. Enlightenment thinkers and later intellectuals, however, held mixed positions towards Cromwell. Some admired his advocacy for parliamentary authority and civic order, while others criticized his authoritarian measures and religious intolerance. His figure became a symbol in debates on governance, liberty, and the balance between moral duty and political power. Literature served as both a medium of support and critique, illustrating the complex interplay between politics and intellectual discourse. This abstract explores Cromwell’s impact on literary production and the nuanced responses of Enlightenment writers to his political and moral legacy.